Posterior extension of palatal rugae as an anatomical limitation for donor soft tissue grafts in a population of western India - Thomas, Bhavana A.; Brahmbhatt, Nilam A.; M. P., Alfas R. (International Journal Of Community Medicine And Public Health, 2025)
Background: Palatal soft tissue graft is a common approach for plastic surgery for oral and periodontal soft tissue augmentation procedures. If the palatal rugae are harvested within a soft tissue graft, they could cause a persistent aesthetic issue. The purpose of this study was to investigate the posterior extension of the palatal rugae bilaterally and its proximity towards the tooth among the population of western India. Methods: 202 Maxillary dental casts from Gujarat with an age range of 20-30 years were examined. The most posterior extension of the bilateral rugae was determined by a standardized periodontal probe. Also, preferred site for soft tissue harvest was subdivided into four regions of interest and the rugae proximity towards tooth was measured. Results: Total 154 (76.23%) and 147 (72.77%) subjects had their palatal rugae extension beyond the mesial end of the maxillary second premolar on the right and left side, respectively. There was no statistically significant association (p>0.05) between the posterior extension of palatal rugae and other factors such as age, gender and palatal shape. In the four regions examined, the distance from the terminal end of rugae to the gingival margin was greater on the right side compared to the left; however, this difference was not statistically significant. Conclusions: Despite a greater percentage of palatal rugae extending beyond the mesial end of the maxillary second premolar on the right side, the rugae proximity towards tooth was less compared to the left side.